Education and test management methods for current and result students’ knowledge control - Мисник, Людмила Дмитрівна (Eastern-European Journal of Enterprise Technologies, 2012)
The specific of education and test technologies management is determined according to the module-credit system of education process organization. Test method for managing the technology, which is based on the mapping of control processes in bipartite graphs is suggested